The Implementation of Using of Land Rights for Industry - Sahlan Sahlan; Rusli Ayyub; Armin K Armin K; Abraham Bekka (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This research aims to know the control over land, either by individuals, collectively or by the state, is only exercised and may only be exercised, if the aim is for the greatest prosperity and justice of the people or for the welfare of the nation and state as much as possible. The research methods was a normative juridical approach and descriptive analytical and highlighted especially in terms of technical legislation. Data collection was carried out with an emphasis on the study of documentation in the library. Field visits were more aimed at checking the application of positive law and to find problems in its implications. The result of the research indicate that there are problems related to the incomplete conceptual preparation in the planning, policy and regulatory stages, caused by the weakness of the quality of planners and legal officials. These weaknesses have caused problems of misunderstanding and inaccuracy in applying the concept, so that the regulatory policies that are drawn up and their implementation deviate a lot from what is expected and have even led to disharmony in society. The product achieved is such that it is not so good, that it will require a difficult effort and take a long time to harmonize it again. Such conditions and problems occur and are found both in the issue of 'state tenure in the National Defense Law, and in the issue of 'land tenure in industrial areas'. The novelty show that in the field of industrial development, the choice of approach is carried out by prioritizing the interests of small companies, medium-sized enterprises and cooperatives in the field of agro-business and agro-industry, without neglecting the presence and role of big entrepreneurs. And in the land acquisition program for the development of an area, a partnership approach should be developed, in such a way that the interests of the people and the good protection of people's rights to land can be paid more attention.